Perbandingan Performans Reproduksi Kuda Lokal dan Turunan Thoroughbred di Kota Payakumbuh - Hendri Hendri; Suardi Suardi; A Mikail (Universitas Andalas, 2012)
This study aimed to compare the performance of reproduction between local horses and descendant of Thoroughbred in Payakumbuh. In this study used a sample of 60 mares productive which have a complete recording. This research was a field research with survey method. Samples were taken by purposive sampling technique. The parameters were observed in between the age of first marriage, old pregnant, and lust after lambing. The results showed that the average age of first marriage in the Local horse was 26.2 ± 8.53 months while on horseback Throughbred derivative obtained at 51.8 ± 14.5 months, the average of pregnant time of Local horse was 323.17 ± 8.55 days while on horseback derivative Throughbred amounted to 324.37 ± 14 185 days and the median lust after lambing on Local horse was at 16.37 ± 9.37 days while on horseback Throughbred derivative obtained at 10.9 ± 6.64 days.